Analysis of Factors Influencing the Behavior of Utilization of Dental and Oral Health Care Among Primary Students - Ni Luh Putu Ayu Wardhani; Agusta Dian Ellina; Agustin Widyowati (STRADA : Jurnal Ilmiah Kesehatan, 2024)
Dental and oral health is an integral part of overall health services. One effort that can be used to improve children's dental and oral health is through self-focused health promotion activities in schools through UKGS. The aim of the research was to determine the factors that influence the behavior of using dental and oral health care among elementary school students in Talok Village, Malang Regency. Observational research design with a cross-sectional approach. The population of all students in Talok, Malang was 145 respondents. The sample was 106 respondents with purposive sampling technique. Independent variables are health center support, school support, parent support, and student knowledge. The dependent variable is beviour of utilization of dental and oral health care among primary students.